ORGANIZATION OF GROUP WORK IN CLASSES IN GEOGRAPHICAL DISCIPLINES - Hanchuk, O.V. (Pedagogy of Higher and Secondary Education, 2009)
In article problems of the organization of group work on occupations from geographical disciplines are considered.